Use of Psychoactive Medication in Short- and Long-term Abstainers from Alcohol. (4th April 2017) - Nalpas, Bertrand; Perney, Pascal; ,
Abstract: Aim: To document the use of prescribed psychoactive medicines in France in patients recovering from alcohol use disorders (AUDs). Method: Survey among short- and long-term abstainers attending groups of French self-help associations for AUDs, recording socio-demographic profile, duration of abstinence, prescription of psychoactive medication and attitudes towards that, and whether or not in medical or psychological follow-up for AUD. Result: Five hundred seventy-five abstainers participated. More than a half had stopped drinking for at least 5 years. About 25% of the very long-term abstainers were still in follow-up. Benzodiazepines, then antidepressants, were the most frequently used medication. Prescriptions of medication decreased with length of abstinence; was always higher in women than in men and in those with a medical follow-up. About 45% claimed that they were 'dependent' on their pills. Ten years after having stopping drinking, 19 and 42.1% of men and women, respectively, were still under medication. Cluster analysis of self-opinion on medication showed that in 30% of the subjects medication seemed to be prescribed for precautionary reasons. Conclusion: Psychoactive medication in France is frequently prescribed for years following alcohol withdrawal. While it is possible that this is over-prescription, and further work in this regard is needed, changes in an on-going treatment for a given patient would need to be cautious. Short summary: Psychoactive medication in alcohol use disorders often prescribed for long-term abstainers in France. Benzodiazepines and antidepressants are the most frequently prescribed drugs. Prescription is more frequent in women and in those subjects having medical follow-up for their alcohol problem. Over-prescription is discussed.